SUPERHERO CHARACTERISTIC COMPARISON BETWEEN 1938 SUPERMAN AND 21ST CENTURY IRON MAN AS A REFLECTION OF THE AMERICAN ERA - PUTRA, ALDILLA YUNIRWAN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Putra, Aldilla Yunirwan.  2014.  Superhero Characteristic  Comparison  between  1938 Superman and 21ST Century Iron Man as A Reflection of the American Era. Program Studi Sastra Inggris, Jurusan Bahasa dan Sastra, Fakultas Ilmu Budaya, Universitas Brawijaya, Pembimbing: (I) M. Andhy Nurmansyah (II) Nurul Laili.  Keywords: American Superhero, Popular Culture, Entertainment, American Society.    Superheroes are wellknown throughout the world, they appear in various medias to amuse the people as their role as entertainment. Most of  superheroes today come  from America, and superhero has become one of the representatives of American society. American superheroes have evolved through time and era along with the American society itself. Since its first appearance, marked with the born of  The Superman, at the times of World War II, American superheroes have managed to surive and merged together with the society and become one of its popular cultures.   This research is studying how American superhero develops his characteristics in its attempt to amuse the people reflected on how the social condition  at that time of consumption. The focus of this research is to compare the  characteristics of  the first American superhero stories with Amercian superhero stories today to find how the American society shaped their superhero stories. The first superhero is represented by The 1938 Superman while the present superhero is represented by The Iron Man as the most controvercial superhero today.   The result of this research is  expressing how the society is reflected within their superhero stories. The 1938 Superman amused his people with hilarious comical and mostly unrealistic. Superman raises the wartime issues and street criminals in his early stories to answer the call of people at that time. While in the other hand, The Iron Man is here to answer the more realistic and critical audience’s demands. Iron Man today appears with more human characteristics  with his  fragility and imperfectness which made him closer to his people.  The difference between these two superheroes has showed that superheroes are developing together with the society, superheroes are there to answer the people’s need of entertainment. Thus it can be concluded that American superhero stories are the reflection of American society itself.